Some New Results in Extended Cone \(b\)-Metric Space - Kour, Iqbal; Saproo, Pooja; Sharma, Shallu; Billawria, Sahil (Communications in Mathematics and Applications, 2024)
The main aspect of this paper is to investigate some topological properties and Kannan-type contractions in extended cone b-metric spaces. Additionally, we have imposed some extra conditions such that a sequence in an extended cone b-metric space becomes a Cauchy sequence. Furthermore, in order to achieve new results the concept of asymptotic regularity has also been utilized.
Keywords: Cone metric space; Extended cone b-metric space; Fixed point; Completeness